A Retrospective Review on Atypical Femoral Fracture: Operative Outcomes and the Risk Factors for Failure. (26th July 2019) - Lai, Yuen Shan; Chau, Jackie Yee Man; Woo, Siu Bon; Fang, Christian; Lau, Tak Wing; Leung, Frankie
Background: Atypical femoral fractures have been demonstrated to have high risks of reoperation and nonunion. The aim of this study is to evaluate whether the quality of reduction following operative fixation of atypical femoral fracture predicts failure. Methods: This is a 6.5-year retrospective review of atypical femoral fractures from 2 centers in a high-income region. A total of 56 patients with 66 fractures met our inclusion criteria. The quality of reduction was evaluated from postoperative films according to Hoskins' modification of Baumgartner criteria for subtrochanteric fractures. Our primary outcome measure was failure of treatment, defined as either reoperation or nonunion at 12 months. Results: There were a total of 8 reoperations (12% of all fractures) and 8 nonunion (12% of all fractures), affecting a total of 12 fractures (18%) in 12 patients (21%). Closed reduction ( P = .04) and poor quality of reduction ( P = .0227 Fisher exact test) are statistically significant risk factors for failure. Conclusions: An aim for anatomical reduction with both <4 mm maximal cortical displacement and <10° angulation can improve the operative outcome of atypical femoral fractures. The addition of open reduction may be beneficial.